The Role of the Temporoparietal Junction in Self-Other Distinction - Quesque, François; Brass, Marcel (Brain topography, 2019)
Being able to discriminate between what originates from ourselves and what originates from others is critical for efficient interactions with our social environment. However, it remains an open question whether self-other distinction is a domain-general mechanism that is involved in various social-cognitive functions or whether specific ‘self-other distinction mechanisms’ exist for each of these functions. On the neural level, there is evidence that self-other distinction is related to a specific brain region at the border of the superior temporal and inferior parietal cortex, the temporoparietal junction (TPJ). Demonstrating that the TPJ plays a role in social processes that require self-other distinction would support the idea of a domain-general mechanism of self-other distinction. In the present paper, we review evidence coming from clinical observations, neuroimaging experiments and a meta-analysis indicating the involvement of the TPJ in various cognitive operations requiring self-other distinction. At the perceptual level, we discuss the human ability to identify one’s own body and to distinguish it from others. At the action level, we review research on the human ability to experience agency and the control of imitative response tendencies. Finally, at the mental-state level, we discuss the ability to attribute mental states to others. Based on this integrative review, we suggest that the TPJ, and in particular its dorsal part, supports a domain general ability to enhance task-relevant representations when self-related and other-related representations are in conflict. Finally, this conception allows us to propose a unifying architecture for the emergence of numerous socio-cognitive abilities.